Fattening of Polish Holstein-Friesian × Limousin Bulls under Two Production Systems and Its Effect on the Fatty Acid Profiles of Different Fat Depots - Monika Sobczuk-Szul (MDPI AG, 2021)
This study was designed to compare the fatty acid (FA) profiles of four types of fat depots from crossbred bulls (Polish Holstein-Friesian × Limousin, PHF × LM) fattened semi-intensively (SI) and intensively (I). Intramuscular fat was most abundant in total polyunsaturated fatty acids (PUFAs), n-3 and n-6 PUFAs, and functional fatty acids C 18:2, C 18:3, C 20:4 and C 20:5 in comparison with the remaining fat types. Furthermore, note that external fat was more abundant in conjugated linoleic acid (CLA) than other fat types. Grass silage fed to cattle during fattening had a beneficial influence on the FA profile of beef, and an increase in the amount of concentrate in the ration did not decrease beef quality.